1996
DOI: 10.1002/(sici)1097-0215(19960103)65:1<112::aid-ijc19>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Impaired tumor growth in colony-stimulating factor 1 (CSF-1)-deficient, macrophage-deficientop/op mouse: Evidence for a role of CSF-1-dependent macrophages in formation of tumor stroma

Abstract: o 1996 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 14 publications
(6 reference statements)
4
63
2
Order By: Relevance
“…TIM and TAM have been reported to produce a variety of cytokines in vivo which support tumor growth, including TGF␤ and MIF (8,14). In the current study, this was extended to demonstrate that treatment of TAM with IL-12 in vitro or in vivo up-regulated IL-15 and IL-18 gene expression and down-regulated TGF␤ and MIF gene expression.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…TIM and TAM have been reported to produce a variety of cytokines in vivo which support tumor growth, including TGF␤ and MIF (8,14). In the current study, this was extended to demonstrate that treatment of TAM with IL-12 in vitro or in vivo up-regulated IL-15 and IL-18 gene expression and down-regulated TGF␤ and MIF gene expression.…”
Section: Discussionsupporting
confidence: 55%
“…Both tumor-infiltrating macrophages (TIM) 3 and tumor-associated macrophages (TAM) have been described as suppressor macrophages that display antiinflammatory and immunosuppressive activities (9,(11)(12)(13). TIM and TAM also display activities, which appear to be required for tumor growth and metastasis, including production of MCP-1, migration inhibitory factor (MIF), and TGF␤ (8,14). Thus, if TIM and TAM retained functional plasticity, they would potentially be useful targets for tumor therapy regimens because redirecting their functional activities could reduce support for tumor metastasis and reduce suppressive influence of the tumor and TAM on the adaptive immune system.…”
Section: Il-12 Rapidly Alters the Functional Profile Of Tumor-associamentioning
confidence: 99%
“…In contrast, overexpression of CSF-1 in the tumour dramatically increased the macrophage density in the primary tumour and this was correlated with an accelerated malignant switch (Lin et al, 2001). Similarly, removal of CSF-1 from transplanted tumours also resulted in an impairment of growth with extensive necrosis and poor vascularisation, phenotypes that could be reversed by treatment of the mice with CSF-1 (Nowicki et al, 1996). These studies have provided strong evidence that TAMs promote the tumour progression to malignancy.…”
Section: Macrophagesmentioning
confidence: 89%
“…2). In response to tumor microenvironments, macrophages elaborate growth factors, and immune suppressive cytokines (3,4), and a growing body of evidence suggests macrophages promote tumor angiogenesis and progression (5)(6)(7)(8)(9)(10)(11)(12). Several preclinical studies have shown tumor growth suppression by chemical or genetic depletion of TAMs (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular relevance, TAM numbers were greatly reduced in developing mammary carcinomas in CSF-1-deficient mice compared with carcinomas in mice with normal CSF-1 expression (6). A role for CSF-1-dependent TAMs in tumor growth was first inferred by the poor growth of Lewis lung carcinomas in CSF-1-deficient mice (7), whereas parenteral administration of recombinant CSF-1 accelerated tumor growth in wild-type mice (16). CSF-1 antisense oligonucleotides or neutralizing antibody have reduced the growth rates of colon, germline, and mammary carcinoma xenografts (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%